2020
DOI: 10.29173/hsi291
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy of Canada's food guide and the barriers of use

Abstract: The landscape of nutrition advice is vast and full of misinformation. A primary source of nutrition advice in Canada comes from the Canadian Food Guide, however, many questions remain regarding the reach and accessibility of the food guide. Specifically, is the population most likely to receive and use this information, the population that needs it the most? Are there barriers to following this guide that Health Canada has failed to address? Is there evidence supporting the efficacy of this food guide in popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Similar to the Brazil Food Guide (Ministry of Health of Brazil, 2014), this revised guide not only made new behavioral recommendations to Canadians but also cautioned about the impact of food marketing (Health Canada, 2021). Some scholars and advocates criticized Canada's Food Guide for failing to consider the affordability and accessibility of culturally appropriate and healthy foods (Dibe, 2020;Duignan, 2019;Wilson & Shukla, 2020). A national survey conducted at the time found that there was a perception among respondents that the recommended foods would cost more and that they did not match people's preferred diets (Charlebois et al, 2019).…”
Section: Background and Contextmentioning
confidence: 99%
“…Similar to the Brazil Food Guide (Ministry of Health of Brazil, 2014), this revised guide not only made new behavioral recommendations to Canadians but also cautioned about the impact of food marketing (Health Canada, 2021). Some scholars and advocates criticized Canada's Food Guide for failing to consider the affordability and accessibility of culturally appropriate and healthy foods (Dibe, 2020;Duignan, 2019;Wilson & Shukla, 2020). A national survey conducted at the time found that there was a perception among respondents that the recommended foods would cost more and that they did not match people's preferred diets (Charlebois et al, 2019).…”
Section: Background and Contextmentioning
confidence: 99%